MSDD: a manually curated database of experimentally supported associations among miRNAs, SNPs and human diseases. Issue Volume 46:Issue D1(2018) (2nd November 2017) - Yue, Ming; Zhou, Dianshuang; Zhi, Hui; Wang, Peng; Zhang, Yan; Gao, Yue; Guo, Maoni; Li, Xin; Wang, Yanxia; Zhang, Yunpeng; Ning, Shangwei; Li, Xia
Abstract: The M iRNA S NP D isease D atabase (MSDD, http://www.bio-bigdata.com/msdd/ ) is a manually curated database that provides comprehensive experimentally supported associations among microRNAs (miRNAs), single nucleotide polymorphisms (SNPs) and human diseases. SNPs in miRNA-related functional regions such as mature miRNAs, promoter regions, pri-miRNAs, pre-miRNAs and target gene 3′-UTRs, collectively called 'miRSNPs', represent a novel category of functional molecules. miRSNPs can lead to miRNA and its target gene dysregulation, and resulting in susceptibility to or onset of human diseases. A curated collection and summary of miRSNP-associated diseases is essential for a thorough understanding of the mechanisms and functions of miRSNPs. Here, we describe MSDD, which currently documents 525 associations among 182 human miRNAs, 197 SNPs, 153 genes and 164 human diseases through a review of more than 2000 published papers. Each association incorporates information on the miRNAs, SNPs, miRNA target genes and disease names, SNP locations and alleles, the miRNA dysfunctional pattern, experimental techniques, a brief functional description, the original reference and additional annotation. MSDD provides a user-friendly interface to conveniently browse, retrieve, download and submit novel data. MSDD will significantly improve our understanding of miRNA dysfunction in disease, and thus, MSDD has the potential to serve as a timely and valuable resource.